A multi-dimensional risk signature for lupus nephritis in systemic lupus erythematosus: integrating symptoms, biochemistry and immune cell profiles - Liu, Xiaoli; Xiao, Zhefeng; Zhang, Xia; Li, Jianfeng; Yuan, Youhua; Li, Na; Zhang, Xiuzhi; Li, Shiqing; Gao, Lan (Frontiers in Immunology, 2025)
BackgroundLupus nephritis (LN) is one of the most severe organ manifestations of systemic lupus erythematosus (SLE). Given its complex pathogenesis and heterogeneous clinical presentation, the clinical management of LN remains challenging. To identify risk factors for LN and provide new insights for its diagnosis and clinical treatment, it is essential to analyze the associations between demographic characteristics, biochemical parameters, clinical features, and immune cell profiles in SLE and LN.MethodsThis retrospective study enrolled 121 SLE patients, including 55 with lupus nephritis (LN-positive) and 66 without LN (LN-negative), along with 121 age- and sex-matched healthy controls. Clinical manifestations and laboratory parameters were extracted from medical records for comparative analysis. Differences between groups were assessed using the Mann-Whitney U test and chi-square test. Spearman correlation analysis and regression modeling were employed to evaluate variable associations and their relationship with LN occurrence.ResultsCompared to the LN-negative cases, LN patients were younger, had higher SLEDAI-2000 scores, ESR, WBC count, 24-hour urine total protein (24h-UTP), anti-dsDNA and ANA titers (AC-1 homogeneous pattern), and Cystatin-C (CysC), but lower C3 complement levels. They exhibited cutaneous manifestations and edema more frequently and arthritis less frequently. Flow cytometry showed higher circulating lymphocytes, CD3+CD8+ T cells, and PD-1+ T cell subsets (CD3+, CD4+, CD8+) in LN individuals. In LN patients, ESR correlated positively with PD-1+ T cell levels. In contrast, in LN-negative cases, anti-dsDNA levels correlated negatively with both age and PD-1+ T cell levels. Similarly, SLEDAI-2000 scores correlated negatively with lymphocytes and PD-1+CD3+ T cells. Multivariate regression analysis identified 24h-UTP, PD-1+CD4+ T cells, SLEDAI-2000 score, and edema as independent risk factors for LN in SLE.ConclusionSignificant differences were observed in both clinical manifestations and serological profiles between LN and LN-negative SLE patients. Notably, elevated PD-1+CD4+ T cells were identified as an independent risk factor for LN development. These findings suggest that abnormal expansion of PD-1+ T lymphocytes may serve as both a diagnostic marker for LN onset and a potential therapeutic target for LN management.